DAYA KETAHANAN FUNGI PATOGEN YANG MENYERANG TANAMAN KOMODITAS HORTIKULTURA SPESIES STRAWBERRY DARI EKSTRAK ETANOL 96% BUNGA KECOMBRANG - Ratna Fitry Yenny; Arti Wahyu Utami; Na’imatul Retno Faizah; Tri Yudianto; Alfina Nurrahman; Octavina Dyah Oentari; Andri Tri Cahyono; Dyah Rohma Wati; Firman Rezaldi; M. Fariz Fadillah (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2022)
Horticultural commodity crops can be prioritized, apart from industrial needs, they can also be utilized by the community because they play a role in facilitating nutritional needs which include fiber, vitamins and protein. The biochemical composition contained in horticultural commodity plants are substances that are essential for the human body. Priorities for horticultural commodity crops to be cultivated by farmers include high economic value, high market opportunities, and high income benefits. Strawberry is a horticultural commodity crop that has quite high economic value. Controlling diseases that have the potential to attack plants is one of the main priorities for plant breeders because until now farmers still control them by using chemicals that are less economical, very excessive, not well maintained, pollute the environment as a negative effect, namely by using pesticides excessively. instant or chemical. The two types of fungal pathogens found in this research to attack strawberry plants include Botrytis cinerea, Colletotrichum acutatum. The solution to overcome the minimal use of synthetic and environmentally friendly pesticides is to use natural ingredients which can reduce the occurrence of quite high side effects in the long term. The solution to overcome the minimal use of synthetic and environmentally friendly pesticides is to use natural ingredients which can reduce the occurrence of quite high side effects in the long term. The natural material used in this research is kecombrang flowers extracted by 96% ethanol. The research carried out was laboratory experimental, namely by providing synthetic antibiotics as a positive control, CMC 1% as a negative control, ethanol extract of kecombrang flowers at 1%, 3% and 5%. The test method for testing this durability is disc diffusion. 96% ethanol extract at all concentrations correlated positively as an antifungal for horticultural commodity plant pathogens in strawberry species. A 5% concentration of 96% ethanol extract is the best treatment when compared to concentrations of 1% and 3%.